Clonality analysis of multifocal papillary thyroid carcinoma by using genetic profiles. Issue 1 (1st April 2016) - Lu, Zheming; Sheng, Jindong; Zhang, Yujie; Deng, Jianhua; Li, Yong; Lu, Aiping; Zhang, Juan; Yu, Huan; Zhang, Min; Xiong, Zikai; Yan, Hai; Diplas, Bill H; et al.
Abstract: Papillary thyroid carcinoma (PTC) is the most common adult thyroid malignancy and often presents with multiple anatomically distinct foci within the thyroid, known as multifocal papillary thyroid carcinoma (MPTC). The widespread application of the next‐generation sequencing technologies in cancer genomics research provides novel insights into determining the clonal relationship between multiple tumours within the same thyroid gland. For eight MPTC patients, we performed whole‐exome sequencing and targeted region sequencing to identify the non‐synonymous point mutations and gene rearrangements of distinct and spatially separated tumour foci. Among these eight MPTCs, completely discordant mutational spectra were observed in the distinct cancerous nodules of patients MPTC1 and 5, suggesting that these nodules originated from independent precursors. In another three cases (MPTC2, 6, and 8), the distinct MPTC foci of these patients had no other shared mutations except BRAF V600E, also indicating likely independent origins. Two patients (MPTC3 and 4) shared almost identical mutational spectra amongst their separate tumour nodules, suggesting a common clonal origin. MPTC patient 7 had seven cancer foci, of which two foci shared 66.7% of mutations, while the remaining cancer foci displayed no common non‐synonymous mutations, indicating that MPTC7 has multiple independent origins accompanied by intraglandular disease dissemination. In this study, we found that 75% of MPTC cases arose as independent tumours, which supports the field cancerization hypothesis describing multiple malignant lesions. MPTC may also arise from intrathyroidal metastases from a single malignant clone, as well as multiple independent origins accompanied by intrathyroidal metastasis. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.